2010 International Joint Conference on Computational Cybernetics and Technical Informatics 2010
DOI: 10.1109/icccyb.2010.5491220
|View full text |Cite
|
Sign up to set email alerts
|

Towards better modeling of supermarkets

Abstract: -In this paper we introduce the supermarket setout problem which aims at finding an appropriate setout of products (i.e. which product should be placed on which position at which shelf) w.r.t. the expected profit, access time (time required to find a product), etc. Finding a good setout of products is important both in the customer-area and in the background store of supermarkets. The admissible setouts are constrained by laws (like food is not allowed to be placed next to chemicals) and "setout traditions" (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…To examine the perceptions of teacher trainers on the lifelong learning, we used the Perceptions of Lifelong Learning Questionnaire, which was developed by Ref. [ 7 ]. After adapting and translating it into the context of our study, this instrument is one dimensional and composed of 9 items (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the perceptions of teacher trainers on the lifelong learning, we used the Perceptions of Lifelong Learning Questionnaire, which was developed by Ref. [ 7 ]. After adapting and translating it into the context of our study, this instrument is one dimensional and composed of 9 items (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Several scholars have identified the factors that can affect lifelong learning abilities, such as the work of [ 6 ] on tendencies for lifelong learning among university students. Reference [ 7 ] investigated perceptions of lifelong learning and suggested that education can be organized to ensure quality and lifelong learning. Reference [ 8 ] found four aspects that can contribute to the development of lifelong learning skills: curricular structure, the institution's resources, learning and instruction, and the assessment system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…'The personhood of the state means that the state can be a legal subject, the holder of rights and duties.' 58 As formulated by the classical authors of state-law positivism, the peculiar nature of state power is due to the fact that it refers to a ruling will, issuing unconditional commands and enforcing its commands by its own power. In a modern state, only the power of the state is a ruling power; individuals or bodies can exert such power only if commissioned by the state.…”
Section: The Public Personhood Of the Statementioning
confidence: 99%
“…In a modern state, only the power of the state is a ruling power; individuals or bodies can exert such power only if commissioned by the state. 59 It does not follow, however, that the public-law personality of the state should be separated from its civil-law one. Buza himself emphasised, following Jellinek, that…”
Section: The Public Personhood Of the Statementioning
confidence: 99%